Cerebral Venous Thrombosis as an Extrahepatic Manifestation of Acute Anicteric Hepatitis A Infection. (17th July 2012) - Zis, Panagiotis; Kontogeorgi, Elli; Karakalos, Dimitrios; Pavlopoulou, Despoina; Sevastianos, Vassilios A.
Abstract : Among the many infective causes of cerebral venous thrombosis (CVT), viral hepatitis has been regarded as a rare associated condition. We report the case of a 31-year-old woman presenting with CVT associated with hepatitis A virus (HAV) infection, outlining probable pathogenic mechanisms. We suggest that hepatitis A serological markers should be routinely included in the investigation of cerebral venous thrombosis of unknown etiology, in nonvaccinated patients with risk factors of a recent HAV exposure.